TAFSIR KEBENCIAN Studi Bias Gender dalam Tafsir Al-Qurān Karya Zaitunah Subhan - Halimatussa’diyah, Halimatussa’diyah (JIA (Jurnal Ilmu Agama), 2015)
The paper objectives are to describe and to anlyze the Zainatunah Subhan view on the exegesis of gender verses in Al Quran. According to her, indeed there is gender bias if the verses are textually interpreted. Otherwise, Al Quran supports the equality of both verses, if the verses are interpreted contextually along with scientific explanation.